Art for beginners. - Cavallaro, Dani (Orient Longman, 2000)
"This critical study of Miyazaki's work begins with an analysis of the visual conventions of manga, Japanese comic books, and anime; an overview of Japanese animated films; and a consideration of the techniques deployed by both traditional cel and computer animation. This section also details Miyazaki's early forays into comic books and animation, and his output prior to his founding of Studio Ghibli. Part Two concentrates on the Studio Ghibli era, outlining the company's development and analyzing the director's productions between 1984 and 2004, including Castle in the Sky, My Neighbor Totoro and his newest, Howl's Moving Castle. Appendices supply information about Studio Ghibli merchandise, Miyazaki's global fan base, and the output of other Ghibli directors."--BOOK JACKET.